The Needs For Public Services Relating To The Legalization of Public Documents In Education - Tan, Winsherly (SASI, 2022)
Introduction: Legalization is legalizing a signature as proof that the document made by the parties was indeed signed by the parties.Purposes of the Research: Indonesia already has regulations in providing good public services, namely Law No. 25 of 2009 concerning Public Services. Indonesia has ratified the Apostille Convention. The aim of this study are to analyze public services in terms of legalizing public documents in Indonesia through Apostille and to analyze the need for legalization of public documents in education through Apostille.Methods of the Research: The research method used is the normative juridical. This study also uses a juridical basis and a theoretical basis. The juridical basis used is Law No. 25 of 2009, Presidential Regulation No. 2 of 2021, Government Regulation of the Republic of Indonesia No. 96 of 2012 and the theoretical basis used is the Legal Benefit Theory by Jeremy Bentham.Results of the Research: The implementation of public services for the legalization of public documents through Apostille has met excellent service standards. The need for public document services in the field of education is also very much needed, especially with the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program. This shows the increasing need for public document legalization services in the education sector.